Experience capitalization: Collective planning from the ground up - Nanda, Rituu B. (Technical Centre for Agricultural and Rural Cooperation, 2019)
I'm based in Delhi and work for an international non-profit organisation called The Constellation. I encourage communities to engage in the Community Life Competence Process (CLCP). This is a process built around a learning cycle where a community takes action and learns from their own experience. The learning then becomes the basis for another round of action and, in turn, learning. The learning cycle can continue indefinitely.